MENINGKATKAN KEMAMPUAN MOTORIK ANAK MELALUI RANGSANGAN AUDIO DI TK TELADAN PERTIWI TUNAS HARAPAN KOTA BUKITTINGGI - Tiara Eka Respati; Susmiarti Susmiarti; Yuliasma Yuliasma (SENDRATASIK UNP, 2017)
AbstractThis article the aim to describe the improvement of children’s motor skills through fun activities, that is audio stimulation. This research was based on the fact that childreen’s had low motor skills. This was due to the lack of creativity and strategy from teachers in creating an activity to develop children’s motor. This research was a Clasroom Action Research (PTK) which took 20 people, 9 boys and 11 girls, as the subject of this research. The techniques of data collection used were observation and documentation. It was conducted in two cycles. Cycle I consisted of three meetings and cycle II was conducted in three meetings. In cycle I, the percentage of the average score of children with good category was thirty-nine percent, while in cycle II, the percentage of the average score of children increased to eighty-five percent. The result of this research showed that the average percentage of children’s motor skills trough audio stimulation increased from 39% in cycle I to 85% cycle II. Their score increased into good in cycle I and became better in children’s motor skills at Teladan Pertiwi Tunas Harapan kindergarten, BukittinggiKeywords: Motor, Stimulation, Dance